EVALUASI ATAS OPTIMALISASI KONTRIBUSI PENDAPATAN ASLI (PAD) TERHADAP PENDAPATAN DAERAH (PATDA) DI DINAS PENDAPATAN DAERAH PROVINSI SUMATERA SELATAN - ASPAHANI .; ERMADIANI . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2013)
This study aims to determine the role of Dispenda in optimizing the contribution revenue to the regional revenue, as well as to determine the factors that inhibit the role of Dispenda of South Sumatra Province in optimizing the revenue (PATDA), and to know what efforts done by The Dispenda of south Sumatra Province in dealing with the factors that inhibit the role. This study is conducted with a qualitative descriptive approach and implemented in Dispenda of South Sumatra ProvinceÂ  by noticing and comparing the target and the realization that has been achieved by the Revenue of South Sumatra Province from 2007 until October 2012, and see how the targets and realization of revenue (PAD ) ranging from motor vehicle tax revenue target (PKB), vehicle ownership transfer tax (BBNKB), vehicle tax on water (PKAA), customs behind the name of the vehicle above the water (BBNKAA), tax collection and utilization of surface water (P3AP), taxes motor vehicle fuel (PBBKB), tax collection and utilization of underground water (P3ABT).From the results, it can be concluded that the contribution of PAD to PATDA almost 50% in achievement, yet PAD particularly regional tax and retribution itself is not optimal. This is due to the unstable economy, people who do not obey the conditions of their obligation to pay taxes, the contribution of BUMN /D/S is not maximized and the related agencies have not done the collection optimally as well as the lack of human resourcesÂ  and enforcement officers in the field. To overcome these obstacles,The Revenue of South Sumatra Province takes measures such as direct billing to the field, conducting a raid on a regular basis, providing mobile Samsat cars, reproducing Samsat posts, improving services and conducting technical guidance to staff regarding materials regulations so it can be socialized easily.